Newborn infants' auditory system is sensitive to Western music chord categories - Virtala, Paula; Huotilainen, Minna; Partanen, Eino; Fellman, Vineta; Tervaniemi, Mari (Frontiers in Psychology, 2013)
Neural encoding of abstract rules in the audition of newborn infants has been recently demonstrated in several studies using event-related potentials (ERPs). In the present study the neural encoding of Western music chords was investigated in newborn infants. Using ERPs, we examined whether the categorizations of major versus minor and consonance versus dissonance are present at the level of the change-related mismatch response (MMR). Using an oddball paradigm, root minor, dissonant and inverted major chords were presented in a context of consonant root major chords. The chords were transposed to several different frequency levels, so that the deviant chords did not include a physically deviant frequency that could result in an MMR without categorization. The results show that the newborn infants were sensitive to both dissonant and minor chords but not to inverted major chords in the context of consonant root major chords. While the dissonant chords elicited a large positive MMR, the minor chords elicited a negative MMR. This indicates that the two categories were processed differently. The results suggest newborn infants are sensitive to Western music categorizations, which is consistent with the authors’ previous studies in adults and school-aged children.